2013
DOI: 10.1016/j.jpsychires.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The CC genotype in the T102C HTR2A polymorphism predicts relapse in individuals after alcohol treatment

Abstract: The serotonin system is hypothesized to contribute to predisposition and course of alcohol dependence. However, the potential association between the T102C polymorphism (rs6313) in the type 2A serotonin receptor (HTR2A) gene and treatment outcomes in alcohol dependence has not been investigated. The aim of the study was to assess the contribution of this genetic polymorphism as a predictor of relapse in relation to other previously identified predictors. A sample of 254 alcohol dependent subjects, were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Decreased activation in the dorsal ACC during error-related processing (stop error versus stop success) predicted relapse in males and females (note that males and females also exhibited some differential activations that predicted relapse: decreased thalamus activation in females; decreased insula activation in males) (Luo et al, 2013). In contrast, in a behavior-only study of treatment-seeking alcohol-dependent individuals, the stop-signal task administered at baseline did not predict 12-month outcome; instead, 12-month outcome was predicted by genetic variation (type 2A serotonin receptor polymorphism) (Jakubczyk et al, 2013). Notable differences between these studies include the use of fMRI and the length of the follow-up period (3- versus 12 months).…”
Section: Part 2: Prediction Of Clinical Outcome In Already-addicted Imentioning
confidence: 71%
“…Decreased activation in the dorsal ACC during error-related processing (stop error versus stop success) predicted relapse in males and females (note that males and females also exhibited some differential activations that predicted relapse: decreased thalamus activation in females; decreased insula activation in males) (Luo et al, 2013). In contrast, in a behavior-only study of treatment-seeking alcohol-dependent individuals, the stop-signal task administered at baseline did not predict 12-month outcome; instead, 12-month outcome was predicted by genetic variation (type 2A serotonin receptor polymorphism) (Jakubczyk et al, 2013). Notable differences between these studies include the use of fMRI and the length of the follow-up period (3- versus 12 months).…”
Section: Part 2: Prediction Of Clinical Outcome In Already-addicted Imentioning
confidence: 71%
“…Those who relapse to alcohol use during treatment may have more disturbed sleep, as compared to abstainers (Brower, ; Conroy et al., ; Currie et al., ; Smith et al., ). In contrast, 2 studies have failed to demonstrate such a relationship with subjective insomnia (Feige et al., ; Jakubczyk et al., ) as measured by the Athens Insomnia Scale and PSQI, respectively; however, the latter study demonstrated an association of relapse with increased sleep EEG β 2 spectral power. It is possible that the use of alcohol as a sleep aid rather than the sleep disturbance itself is associated with relapse, as demonstrated in a recent study (Kolla et al., ).…”
Section: Resultsmentioning
confidence: 94%
“…This study did not find an association between sleep disturbances and relapse at 12 months (p ¼ .12). 5 Finally, a study examining the correlation between subjective and objective measures of sleep in alcoholic patients enrolled in a randomized control trial of gabapentin to prevent alcohol relapse found no association between sleep variables measured by sleep logs and drinking over 12 weeks (N ¼ 18). 6 In comparison to these previous studies, our cohort was relatively large with a reasonable follow-up rate of 61%.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia as measured by Athens Insomnia Scale was not associated with relapse over 12 months in a study examining gene polymorphisms and relapse risk in 254 alcohol-dependent subjects. 5 Also, sleep variables recorded using a sleep log were not associated with relapse over 12 weeks in a study examining the correlation between subjective and objective sleep measures in 18 recovering alcoholics. 6 Most of these studies that examined the relationship between sleep disturbances and alcohol relapse were limited either by small sample sizes (low power) and/or by the use of questionnaires which are not well validated for measuring sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%